Gangguan Muskuloskeletal pada Mahasiswa Klinik Kedokteran: Studi Cross-Sectional Tentang Prevalensi dan Faktor Risiko - Indra Harianto Rante; Hendrikus Masang Ban Bolly; Gerson A. Warnares; Novianto M (Pusat riset dan Inovasi Nasional, 2025)
Musculoskeletal disorders (MSDs) represent a prevalent health issue among clinical medical students, with global studies reporting incidence rates of 73% in India and 81.9% in Saudi Arabia. Pain is most frequently reported in the neck, lower back, and shoulder areas. However, similar data from Indonesia, particularly Papua, remains limited. This study aims to identify the prevalence and risk factors of MSDs among clinical medical students at the Faculty of Medicine, Cenderawasih University. The research employed a cross-sectional design with a sample of 78 clinical students selected through purposive sampling. Data collection utilized the Standardized Nordic Musculoskeletal Questionnaire (NMQ) to measure prevalence and the Nordic Body Map to localize pain. Data analysis used Chi-Square test to evaluate the relationship between risk factors (such as Body Mass Index/BMI and physical activity) and musculoskeletal complaints. Results showed the majority of respondents were female (74.4%) and aged ≥25 years (51.3%). Most respondents experienced pain at the